2018
DOI: 10.7759/cureus.3099
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaveric Case of a Circular Torcular Herophili

Abstract: The torcular Herophili is formed by the joining of the straight sinus, superior sagittal sinus, and transverse sinus. The anatomic configuration of the torcular Herophili is highly variable. In the current literature, classification systems define up to nine subtypes of the torcular Herophili. The frequency of prevalence of these anatomical variants is also variable. Herein is a case report of a circularly-shaped torcular Herophili found during cadaveric dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The cerebral venous system is far more variable than the cerebral arterial system, differing not only among individuals but also between hemispheres in the same brain. This makes it difficult to classify the cerebral veins [ 6 , 7 ]. In contrast to the arterial system, the venous drainage of the brain is only partly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral venous system is far more variable than the cerebral arterial system, differing not only among individuals but also between hemispheres in the same brain. This makes it difficult to classify the cerebral veins [ 6 , 7 ]. In contrast to the arterial system, the venous drainage of the brain is only partly understood.…”
Section: Discussionmentioning
confidence: 99%
“…A second case was reported by Lake et al in a cadaveric case. 2 Herein, we report a case of circular torcula Herophili presenting with headache.…”
Section: Introductionmentioning
confidence: 96%
“…Tardieu et al reported a previously unreported variant of the torcular herophili with a circular con guration along with absent right transverse sinus [2]. A second case was reported by Lake et al in a cadaveric case [3] 3 . Herein, we report a case of circular torcula herophili presenting with headache.…”
Section: Introductionmentioning
confidence: 97%